(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Custodial violence remains a pervasive issue in India, representing a blatant violation of human rights and a threat to the principles of justice and accountability. This research paper aims to comprehensively analyze the prevalence, underlying causes, and implications of custodial violence in India, with a specific focus on its direct contravention of human rights principles. The study employs a multi-faceted approach, integrating qualitative and quantitative methods to present a thorough assessment of the problem. Extensive literature reviews, official reports, and case studies on instances of custodial violence are analyzed to unveil the patterns and systemic factors that perpetuate this disturbing phenomenon. The research examines custodial violence not only as an isolated act but as a manifestation of deeper institutional flaws within the Indian criminal justice system. Drawing on international human rights standards, the paper evaluates the rights most frequently violated during custodial violence, including the right to life, liberty, and security of person, the prohibition of torture and cruel, inhuman, or degrading treatment, and the right to a fair trial. By highlighting these violations, the research underscores the urgent need for comprehensive legal reforms and the strengthening of law enforcement oversight mechanisms.